Case Study : Fixfone Enterprise / Amir Hamzah Abdul Halim - Abdul Halim, Amir Hamzah (2021)
This is an attempt to know how the theories can be applied to practical situation. As a student in UiTM Kota Bharu, it is a part of study for everyone from CS241 to undergo a case study project in semester 6. So, for this purpose I make a decision to to do some research in Fixfone Enterprise for company analysis project. In the first part of the project report, the general information of the company has been collected. Information is gathered through the primary and secondary source as well. In the second part of the report, contains the specialized subject study. Objective of the project is to work on the background, organizational structure and services that Fixfone Enterprise provides. The company located at Bagan Ajam,Pulau Pinang is basically a store for mobile store that provide phone/laptop service and selling mobile phone and it start operate since 2018.En. Amier Zikri as the owner (22 years old) start the business with limited knowledge about phone.He only provide service for battery changing for android and apple user.After a year start the business and he learn more about mobile industry,he build a company and hired a assistance to run a mobile store and now he have 3 employees to operate the business. Fixfone company popular among students and teenagers in area Butterworth because of the good service and the reasonable price for every service.I do some observation from the previous customers,and looking for their feedback,majority of the customers give positive feedback for Fixfone service. Next, I study about the services that the company provide and other supporting services in order to maintain the stability of the company, as well as business, marketing and its operational strategy used by the company to promote their services which quite interesting. Lastly, I do some research about the company financial achievements regarding how they manage their financial as well as achievements gain from the financial management. Goals indicate what a business unit wants to achieve. Strategy is an action plan for getting the goals. Every business must design a strategy for achieving its goals, consisting of a marketing strategy, and an effective management. In this case study, I analysed the strength, weaknesses, opportunities and threats of this company in real business world by using SWOT analysis.